Estimation of parameters and survival function for a proposed mixed distribution using some estimation methods by simulation - Abdulhussein, Ghufran (The Gulf Economist, 2022)
This research aims to propose a model for probability distribution (Power Function – Truncated Burr III). The proposed model was formulated with finding some mathematical and statistical properties of the distribution. Then, its parameters and survival function for the proposed distribution (MPF-TBIII) were estimated using the method of Maximum Likelihood (MLE), and the Least Squares (OLS). It was also concluded that the Least Squares were the best in estimating the survival function for the large sample size.